Can Cognitive Speed of Processing Training Improve Everyday Functioning Among Older Adults With Psychometrically Defined Mild Cognitive Impairment? - Valdés, Elise G; Andel, Ross; Lister, Jennifer J; Gamaldo, Alyssa; Edwards, Jerri D (Journal of aging and health, 2019)
OBJECTIVE: The aim of these secondary analyses was to examine cognitive speed of processing training (SPT) gains in cognitive and everyday functioning among older adults with psychometrically defined mild cognitive impairment (MCI). METHOD: A subgroup of participants from the Staying Keen in Later Life (SKILL) study with psychometrically defined MCI ( N = 49) were randomized to either the SPT intervention or an active control group of cognitive stimulation. Outcome measures included the Useful Field of View (UFOV), Road Sign Test, and Timed Instrumental Activities of Daily Living (IADL) Test. A 2 × 2 repeated-measures MANOVA revealed an overall effect of training, indicated by a significant group (SPT vs. control) by time (baseline vs. posttest) interaction. RESULTS: Effect sizes were large for improved UFOV, small for the Road Sign test, and medium for Timed IADL. DISCUSSION: Results indicate that further investigation of cognitive intervention strategies to improve everyday functioning in patients with MCI is warranted.
Keywords: Cognitive Dysfunction; cognitive training; Activities of Daily Living; Humans; lidé; Cognitive Behavioral Therapy; activities of daily living; neuropsychologické testy; Female; Male; kognitivní dysfunkce; činnosti denního života; mužské pohlaví; Aged; ženské pohlaví; kognitivně behaviorální terapie; Neuropsychological Tests; mild cognitive impairment; senioři